Chinese and Australians showed difference in mental time travel in emotion and content but not specificity - Chen, Xing-Jie; Liu, Lu-Lu; Cui, Ji-Fang; Wang, Ya; Shum, David H. K.; Chan, Raymond C. K. (Frontiers in Psychology, 2015)
Mental time travel refers to the ability to recall episodic past and imagine future events. The present study aimed to investigate cultural differences in mental time travel between Chinese and Australian university students. A total of 231 students (108 Chinese & 123 Australians) participated in the study. Their mental time travel abilities were measured by the Sentence Completion for Events from the Past Test (SCEPT) and the Sentence Completion for Events in the Future Test (SCEFT). Results showed that there were no cultural differences in the number of specific events generated for the past or future. Significant differences between the Chinese and Australian participants were found mainly in the emotional valence and content of the events generated. Both Chinese and Australian participants generated more specific positive events compared to negative events when thinking about the future and Chinese participants were more positive about their past than Australian participants when recalled specific events. For content, Chinese participants recalled more events about their interpersonal relationships, while Australian participants imagined more about personal future achievements. These findings shed some lights on cultural differences in episodic past and future thinking.